Breast feeding knowledge, attitude and perspective in immediate postnatal mothers - Shetty, Vishma H. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The aim of the study is to understand the knowledge, attitude and practice of breastfeeding among postnatal mothers and optimize the breast feeding practices and overcome various factors that hinder and influence the full realization of benefits of breast feeding. Methods: The study was conducted in the postnatal ward of Rajarajeswari medical college and hospital, Bangalore. 500 postnatal mothers were included. A structured interview schedule was prepared to collect sociodemographic data, perceptions, knowledge, attitude and practices of mothers regarding breastfeeding. Data was collected by interviewing mothers (in their own language) using proforma. Results: About 100% of mothers and newborn infant have skin to skin contact within one hour of an uncomplicated vaginal delivery. Majority of the mothers knew about the importance of breast feeding for babies and herself. Only 17% of the mothers were working in our study and majority of them had resigned from their work as there was no option of maternity leave and baby friendly work environment at their working places. 69% intended to breastfeed up to 6 months. 23% mothers discarded colostrum and 11% gave prelacteal feeds to their babies. Conclusions: The mothers should be encouraged and reinforced about the benefits of breastfeeding for both baby and herself. The workplace condition has to be improved and make it more breast feeding friendly. The study also will assist the health care providers and community workers to understand the attitude and practice in the area and help them to prioritize and focus on these aspects and decrease the incidence of suboptimal feeding practices.